IMPLEMENTATION OF TECHNOLOGY-BASED LEARNING MEDIA: STUDENT ATTITUDES AND EXPERIENCES - Ririn Meylinda Purwasari; Ine Rahayu Purnamaningsih (IKIP Siliwangi, 2022)
It is an undeniable fact that nowadays most of the students can enjoy new technology that can be used without any time limit which can be used anytime and anywhere. This allows them to apply these technological developments in their lives, especially in the field of education or learning. This study aims to determine the attitudes and experiences of students in implementing technology-based media innovation in the learning process. The method and design in this research is to use descriptive qualitative research conducted through interviews and tracing relevant literature to answer this research and set forth in a descriptive form. The results of this study indicate that the implementation of technology-based media is very helpful for students in the learning process. The development of technology also increases the number of media that can be used. This makes students explore a lot of learning materials and their knowledge with a wide scope. The application of this media is considered effective to increase student interest in learning, with more and more media making the learning process more enjoyable. It is inevitable that this implementation has obstacles, however, it does not reduce students' initiative to apply technology to their learning process. The use of this technology also encourages students' creativity in the learning process. Apart from being a learning media, technology can be a tool and media in distributing material and providing convenience in communicating learning which of course has an effect on improving the quality of learning. Keywords: Technology, Learning Media, Implementation, Attitude, Experience